2006
DOI: 10.1152/jn.00928.2005
|View full text |Cite
|
Sign up to set email alerts
|

Functional Organization of Ganglion Cells in the Salamander Retina

Abstract: Segev, Ronen, Jason Puchalla, and Michael J. Berry II. Functional organization of ganglion cells in the salamander retina. J Neurophysiol 95: 2277-2292, 2006. First published November 23, 2005 doi:10.1152/jn.00928.2005. Recently, we reported a novel technique for recording all of the ganglion cells in a retinal patch and showed that their receptive fields cover visual space roughly 60 times over in the tiger salamander. Here, we carry this analysis further and divide the population of ganglion cells into func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
162
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(177 citation statements)
references
References 52 publications
(75 reference statements)
13
162
1
Order By: Relevance
“…At the temporal maximum of the STA, a general two-dimensional Gaussian was fit to the spatial response profile. Similar to recordings from other species using comparable stimulation conditions (Devries and Baylor, 1997;Segev et al, 2006), receptive field surrounds were weak in our recordings, and fitting receptive field profiles with a difference of Gaussians offered no significant improvement and were therefore not included in the present analysis. The radius of the receptive field (r) was defined as follows:…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…At the temporal maximum of the STA, a general two-dimensional Gaussian was fit to the spatial response profile. Similar to recordings from other species using comparable stimulation conditions (Devries and Baylor, 1997;Segev et al, 2006), receptive field surrounds were weak in our recordings, and fitting receptive field profiles with a difference of Gaussians offered no significant improvement and were therefore not included in the present analysis. The radius of the receptive field (r) was defined as follows:…”
Section: Discussionmentioning
confidence: 67%
“…This was achieved by making vectors representing the respective parameters unit length, before concatenating them and subjecting them to k-means clustering. Inclusion of the autocorrelation function and/or responses to diffuse light steps did not change our classification (Segev et al, 2006). Instead, it revealed that responses of fast ON cells were more sustained than for medium ON cells, and responses of biphasic OFF cells were more sustained compared with those of monophasic OFF cells (data not shown).…”
Section: Identification Of Functional Rgc Types In Micementioning
confidence: 84%
See 1 more Smart Citation
“…The responses of different cells are precisely timed in the retina, with different amacrine and ganglion cells having distinct temporal responses with respect to light (6)(7)(8)(9). Inhibitory transmission to ganglion cells is known to have different effects, including reducing activity (6,10), or increasing activity through disinhibition (11)(12)(13)(14).…”
mentioning
confidence: 99%
“…S1 for how it is derived. If RFs are described as Gaussians, then the width of the Gaussian is found to be ϷL/2 in different species and types of retinal ganglion cells (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12) (Fig. 1A), with the exception of some cell types in the salamander retina (5).…”
mentioning
confidence: 99%